2020
DOI: 10.1101/2020.08.31.276311
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stability Analysis of a Signaling Circuit With Dual Species of Gtpase Switches

Abstract: GTPases are molecular switches that regulate a wide range of cellular processes, such as organelle biogenesis, position, shape, and function, vesicular transport between organelles, and signal transduction. These hydrolase enzymes operate by toggling between an active (”ON”) guanosine triphosphate (GTP)-bound state and an inactive (”OFF”) guanosine diphosphate (GDP)-bound state; such a toggle is regulated by GEFs (guanine nucleotide exchange factors) and GAPs (GTPase activating proteins). Here we dissect a net… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…The net result of this is that the closed loop feedback control allows for a tighter alignment of secretion with respect to EGF by 'stretching' out the dose-response curve across series of switches to propagate the signal from the extracellular space to the interior of the cell (Figure 5B). Because the stability behavior of a mathematically simpler version of this closed loop system of coupled GTPases showed that coupling afforded a wide range of steady states (53), it is tempting to speculate that the coupled system allows flexibility in responses over a wide range of stimuli ( Figure 5C).…”
Section: Discussionmentioning
confidence: 99%
“…The net result of this is that the closed loop feedback control allows for a tighter alignment of secretion with respect to EGF by 'stretching' out the dose-response curve across series of switches to propagate the signal from the extracellular space to the interior of the cell (Figure 5B). Because the stability behavior of a mathematically simpler version of this closed loop system of coupled GTPases showed that coupling afforded a wide range of steady states (53), it is tempting to speculate that the coupled system allows flexibility in responses over a wide range of stimuli ( Figure 5C).…”
Section: Discussionmentioning
confidence: 99%